Method for producing recycled (meth)acrylic resin, method for producing recycled (meth)acrylic resin film, and method for producing recycled optical film

JP2024005125A5Inactive Publication Date: 2025-02-20NIPPON SHOKUBAI CO LTD
View PDF -1 Cites 0 Cited by

Patent Information

Application Number
JP2022105166
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-06-29
Publication Date
2025-02-20
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a technique to recycle an optical film.SOLUTION: A manufacturing method of a recycled (meth)acrylic resin film includes: a step of depolymerizing an optical film including a (meth)acrylic resin film and a first primer layer laminated, to obtain a (meth)acrylic acid ester monomer; and a step of polymerizing a (meth)acrylic acid ester monomer or the (meth)acrylic acid monomer and a monomer group containing a monomer other than the (meth)acrylic acid monomer to obtain a recycled (meth)acrylic resin. The optical film includes a (meth)acrylic resin film and a primer layer laminated, and the (meth)acrylic resin film includes a same kind of resin as a binder resin included in the primer layer.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing recycled (meth)acrylic resin, a method for producing recycled (meth)acrylic resin film, a method for producing recycled optical film, and an optical film. [Background technology]

[0002] (Meth)acrylic resins, including (meth)acrylic polymers such as polymethyl methacrylate (PMMA), have excellent optical properties such as light transmittance, and also have an excellent balance between mechanical strength, moldability, and surface hardness. For this reason, the application of (meth)acrylic resins to optical films incorporated in image display devices such as liquid crystal display devices, plasma display panels, and organic electroluminescence display devices is being promoted.

[0003] An optical film may be laminated with other functional films when used. For example, a polarizer protective film, which is one type of optical film, is usually laminated with a polarizer to form a polarizing plate.

[0004] An example of an optical film is one in which a primer layer is formed on the surface of a (meth)acrylic resin film. The primer layer is a layer that improves the adhesion between the (meth)acrylic resin film and other functional resin films. For example, Patent Document 1 describes a polarizing plate including a polarizer and a polarizer protective film bonded to at least one surface of the polarizer via an adhesive.

[0005] Patent Document 2 describes a polarizer protective film having a (meth)acrylic resin film and a primer layer. The primer layer is formed of an easy-adhesive composition containing a urethane resin and fine particles. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2007-127893 A [Patent Document 2] JP 2010-55062 A Summary of the Invention [Problem to be solved by the invention]

[0007] (Meth)acrylic resin films used in optical films are required to have high optical properties such as total light transmittance and haze value. For this reason, it is desirable that the (meth)acrylic resin film does not contain any substances (foreign matter) other than the (meth)acrylic resin. For this reason, optical films containing foreign matter or optical films not satisfying the above required properties have conventionally been discarded without being reused.

[0008] The reason why optical films have been discarded without being reused is as follows. That is, the optical film has a (meth)acrylic resin film and a primer layer laminated on the (meth)acrylic resin film. The primer layer contains, for example, a binder resin other than (meth)acrylic resin and fine particles. Since an optical film having a primer layer contains a substance other than (meth)acrylic resin, it was thought that if such an optical film is reused in production, foreign matter will be mixed into the obtained optical film to a non-negligible extent. The present inventors have focused on this problem, which has not been considered, without being bound by conventional knowledge. The present invention aims to provide a technology for reusing optical films. [Means for solving the problem]

[0009] In view of the above circumstances, the present inventors conducted extensive research and completed the inventions described below in [1] to

[13] . [1] A method for producing a recycled (meth)acrylic resin, comprising: a step of depolymerizing an optical film having a (meth)acrylic resin film and a first primer layer laminated thereon to obtain a (meth)acrylic acid ester monomer; and a step of polymerizing the (meth)acrylic acid ester monomer, or a monomer group including the (meth)acrylic acid ester monomer and a monomer other than the (meth)acrylic acid ester monomer, to obtain a recycled (meth)acrylic resin. [2] The method for producing a recycled (meth)acrylic resin according to [1], wherein in the step of obtaining the (meth)acrylic acid ester monomer, the optical film is depolymerized and then the (meth)acrylic acid ester monomer is purified by distillation to obtain the (meth)acrylic acid ester monomer. [3] The method for producing a recycled (meth)acrylic resin according to [1] or [2], wherein the (meth)acrylic acid ester monomer contains methyl methacrylate. [4] A method for producing a recycled (meth)acrylic resin film, comprising the steps of obtaining a recycled (meth)acrylic resin by the production method according to any one of [1] to [3], and molding the recycled (meth)acrylic resin to obtain a recycled (meth)acrylic resin film. [5] A method for producing a recycled (meth)acrylic resin film, comprising: a step of melting an optical film having a (meth)acrylic resin film and a first primer layer laminated thereon to obtain first pellets; and a step of producing a recycled (meth)acrylic resin film from a film raw material containing the first pellets and second pellets that contain a (meth)acrylic resin and are substantially free of components contained in the first primer layer. [6] The method for producing a recycled (meth)acrylic resin film according to [5], wherein a ratio of the first pellets to the second pellets in the film raw material is determined so that a haze value A [%] of the recycled (meth)acrylic resin film and a haze value B [%] of a reference film obtained from the second pellets and having the same thickness as the recycled (meth)acrylic resin film satisfy A≦2B. [7] A method for producing a recycled (meth)acrylic resin film, comprising a step of removing the primer layer from an optical film having a (meth)acrylic resin film and a first primer layer laminated thereon, and the following step (i) or step (ii): (i) a step of melting the (meth)acrylic resin film from which the first primer layer has been removed to obtain pellets, and a step of obtaining a recycled (meth)acrylic resin film from a film raw material containing the pellets, and (ii) a step of filtering a solution of the (meth)acrylic resin film from which the first primer layer has been removed to obtain a filtrate, and a step of obtaining a recycled (meth)acrylic resin film from a film raw material containing the filtrate. [8] A method for producing a recycled optical film, comprising: a step of obtaining the recycled (meth)acrylic resin film by the production method described in any one of [4] to [7]; and a step of laminating a second primer layer containing the same type of binder resin as the resin contained in the first primer layer onto the recycled (meth)acrylic resin film. [9] An optical film comprising a (meth)acrylic resin film and a primer layer laminated thereon, the (meth)acrylic resin film containing the same type of resin as the binder resin contained in the primer layer.

[10] The optical film according to [9], wherein the (meth)acrylic resin film contains at least one resin selected from a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin as the same type of resin as the binder resin contained in the primer layer.

[11] The optical film according to

[10] , wherein the (meth)acrylic resin film contains at least one selected from a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin in an amount of 0.02% or less in total by mass.

[12] A (meth)acrylic resin film comprising a (meth)acrylic resin and at least one resin selected from a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin, wherein the content of the at least one resin by mass is 0.02% in total.

[13] The (meth)acrylic resin film according to

[12] , comprising at least one selected from a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin only inside in the thickness direction. Effect of the Invention

[0010] According to the present invention, a technique for recycling optical films can be provided. [Brief description of the drawings]

[0011] [Figure 1A] FIG. 1A is a process diagram illustrating a method for producing a recycled (meth)acrylic resin according to a first embodiment. [Figure 1B] FIG. 1B is a process diagram illustrating the method for producing the recycled optical film according to the first embodiment. [Diagram 2] FIG. 2 is a process diagram illustrating a method for producing a recycled (meth)acrylic resin film according to the second embodiment. [Diagram 3] FIG. 3 is a process diagram illustrating a method for producing a recycled (meth)acrylic resin film according to a third embodiment. [Figure 4] FIG. 4 is a process diagram illustrating a method for producing a recycled (meth)acrylic resin film according to a fourth embodiment. [Diagram 5] FIG. 5 is a cross-sectional view illustrating an example of an optical film. [Figure 6] FIG. 6 is a cross-sectional view showing another example of a recycled (meth)acrylic resin film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. The present invention is not limited to the following embodiment.

[0013] (First embodiment) 1A is a process diagram illustrating a method for producing a recycled (meth)acrylic resin according to the first embodiment. In this specification, "recycled (meth)acrylic resin" refers to a (meth)acrylic resin produced by reusing optical films. In addition, "(meth)acrylic" is used as a term that includes acrylic and methacrylic.

[0014] In step S11, the optical film is crushed into chips. By crushing the optical film used as a raw material into chips, the raw material can be easily handled in the depolymerization. Note that step S11 may be omitted.

[0015] An example of the optical film used in step S11 is a nonstandard optical film. The nonstandard optical film is a film that does not meet the required optical properties or required length. Another example of the optical film used in step S11 is a defective optical film. The defective optical film is a film in which foreign matter is mixed in or adhered to the film during the manufacturing process of the optical film. Alternatively, the defective optical film is a film in which a winding shift occurs when the film is wound into a film roll during the manufacturing of the optical film, and wrinkles and scratches occur due to the winding shift. Yet another example of the optical film used in step S11 is a scrap optical film generated after cutting a predetermined size of optical film from a large-sized optical film during the manufacturing of the optical film. In step S11, the nonstandard optical film, the defective optical film, and the scrap optical film can be used as raw materials. In addition, in step S11, a (meth)acrylic resin film without a primer layer applied may also be crushed. Such a (meth)acrylic resin film may be one on which a primer layer cannot be applied for manufacturing reasons during the production of an optical film.

[0016] The optical film used in step S11 is a film in which a (meth)acrylic resin film and a first primer layer are laminated. The optical film has a structure in which a first primer layer is formed on at least one main surface of a (meth)acrylic resin film. In this specification, "main surface" means the surface of a film or layer having the widest area. The first primer layer contains a resin of a different type from the (meth)acrylic resin as a binder resin. In this specification, "different type" means that they are not the same type. The meaning of "same type" and specific examples of binder resins will be described later. The first primer layer may contain fine particles. Specific examples of fine particles will also be described later.

[0017] In step S12, the optical film is depolymerized. In detail, the (meth)acrylic polymer contained in the (meth)acrylic resin film constituting the optical film is depolymerized. This makes it possible to obtain a (meth)acrylic acid ester monomer. The depolymerization can be carried out, for example, by heating the optical film in a heating furnace, a twin-screw kneader, or the like.

[0018] The depolymerization of the optical film may be carried out at a temperature at which a (meth)acrylic acid ester monomer is produced. The temperature at which the optical film is depolymerized may be 300 to 450°C, or 350 to 400°C. By depolymerizing the optical film, a (meth)acrylic acid ester monomer can be obtained. However, a monomer other than the (meth)acrylic acid ester monomer may be obtained together with the (meth)acrylic acid ester monomer. Furthermore, an oligomer composed of a dimer, trimer, or the like of this monomer may be obtained together with the (meth)acrylic acid ester monomer.

[0019] The decomposition product can be discharged as a gas from the reaction vessel and collected. In this case, at least one component contained in the first primer layer can remain in the reaction vessel as a solid or liquid. The at least one component contained in the first primer layer can include a binder resin, fine particles, etc. The decomposition product discharged as a gas can be collected as a liquid such as a condensate.

[0020] The binder resin may be at least one selected from urethane resin, cellulose resin, polyol resin, polycarboxylic acid resin, and polyester resin. The fine particles may be organic particles or inorganic particles. The organic particles are, for example, particles containing an organic cross-linked polymer such as a vinyl cross-linked polymer. The inorganic particles are, for example, silica particles, alumina particles, titania particles, and zirconia particles. The inorganic particles may be glassy particles.

[0021] In the step of obtaining the (meth)acrylic acid ester monomer, the optical film may be depolymerized and then purified by distillation to obtain the (meth)acrylic acid ester monomer. By purifying the decomposition product, the purity of the recovered (meth)acrylic acid ester monomer can be improved.

[0022] In the step of obtaining the (meth)acrylic acid ester monomer, the generation of the decomposition product by depolymerization of the optical film and the distillation of the decomposition product may be performed continuously. In other words, the depolymerization and distillation may be performed continuously using an apparatus in which a reaction vessel for depolymerization and a distillation vessel for purification are connected to obtain the (meth)acrylic acid ester monomer. In addition, in the step of obtaining the (meth)acrylic acid ester monomer, the decomposition product by depolymerization of the optical film may be recovered from the reaction vessel, the recovered decomposition product may be introduced into a distillation vessel not connected to the reaction vessel, and the recovered decomposition product may be heated again in the distillation vessel and purified by distillation.

[0023] The decomposition product includes a (meth)acrylic acid ester monomer. The decomposition product may include a (meth)acrylic acid ester monomer as a main component. In this specification, the term "main component" refers to a component that is contained in the largest amount by mass.

[0024] The (meth)acrylic acid ester monomer may contain methyl methacrylate (MMA). Methyl methacrylate is suitable for recovery and reuse. Methyl methacrylate is also a component that can contribute to improving the transparency of the recycled (meth)acrylic resin film. The recycled (meth)acrylic resin film means a (meth)acrylic resin film obtained by reusing an optical film. The decomposition product may contain, in addition to methyl methacrylate, an oligomer composed of a dimer, trimer, etc. of methyl methacrylate. The decomposition product may contain methyl methacrylate as a main component, or may contain only methyl methacrylate.

[0025] Next, in step S13, the (meth)acrylic acid ester monomer or a monomer group containing the (meth)acrylic acid ester monomer is polymerized. The monomer group contains a monomer other than the (meth)acrylic acid ester monomer as well as the (meth)acrylic acid ester monomer. This results in a recycled (meth)acrylic resin. Here, a commercially available (meth)acrylic acid ester monomer may be added in any amount to the (meth)acrylic acid ester monomer or the monomer group containing the (meth)acrylic acid ester monomer for polymerization.

[0026] The recycled (meth)acrylic resin may contain, for example, other (meth)acrylic polymers, other thermoplastic polymers, and additives. The mixing method is, for example, extrusion kneading or mixing in a solution state. For extrusion kneading, for example, an omnimixer, a single screw extruder, a twin screw extruder, and a pressure kneader can be used.

[0027] The recycled (meth)acrylic resin contains a (meth)acrylic polymer. The content of the (meth)acrylic polymer in the recycled (meth)acrylic resin may be 30% by weight or more, 50% by weight or more, 70% by weight or more, 90% by weight or more, or 95% by weight or more.

[0028] 1B is a process diagram illustrating the method for producing a recycled optical film according to the first embodiment. In step S14, the recycled (meth)acrylic resin is molded to obtain a recycled (meth)acrylic resin film. That is, the recycled (meth)acrylic resin is used to obtain a recycled (meth)acrylic resin film. This makes it possible to manufacture a recycled (meth)acrylic resin film by reusing the optical film. Methods for obtaining a recycled (meth)acrylic resin film using recycled (meth)acrylic resin include solution casting, melt extrusion, melt pressing, calendaring, and compression molding.

[0029] In step S15, a second primer layer is laminated on the recycled (meth)acrylic resin film. This produces a recycled optical film. The second primer layer facilitates bonding of the recycled (meth)acrylic resin film to other films such as a polarizing plate.

[0030] The second primer layer may contain the same type of binder resin as the binder resin contained in the first primer layer. In this specification, the term "same type" means the same family, but does not require the composition to be the same. Therefore, "same type of binder resin" means binder resins classified into the same family based on the type of monomer and / or mutual bonding. For example, two binder resins that contain polymers that are not completely the same monomer but are both classified as polyurethanes are both classified as urethane resins, which are the same family of resins, and therefore correspond to the same type of binder resin. It should be noted that the "second" in the second primer layer does not mean that two primer layers are formed on one optical film. For convenience of explanation, the primer layer in the reused optical film is referred to as the first primer layer, and the primer layer in the manufactured optical film (recycled optical film) is referred to as the second primer layer, simply to distinguish them.

[0031] The second primer layer may contain the same type of fine particles as the fine particles contained in the first primer layer. "The same type of fine particles" means fine particles classified into the same system based on the components of the fine particles. For example, two fine particles that do not have the same amount of impurities but both contain silica as the main component are both classified as silica fine particles, and therefore are the same type of fine particles.

[0032] The second primer layer is formed on the recycled (meth)acrylic resin film, for example, by a coating step and a drying step. The coating step is a step of coating a primer composition on the surface of the recycled (meth)acrylic resin film to form a coating film of the composition. The drying step is a step of drying the coating film to form a second primer layer on the (meth)acrylic resin film. The primer composition contains a resin having high adhesion properties and fine particles. The resin having high adhesion properties may be a resin that functions as a binder resin.

[0033] Second embodiment 2 is a process diagram illustrating a method for producing a recycled (meth)acrylic resin film according to the second embodiment. In step S21, the optical film is crushed into chips. By chipping the optical film used as a raw material, the raw material can be easily handled during melting. Step S21 is similar to step S11 described in the first embodiment, and therefore a description thereof will be omitted. Note that step S21 may be omitted.

[0034] The optical film is a film in which a (meth)acrylic resin film and a first primer layer are laminated. The first primer layer contains a type of resin different from the (meth)acrylic resin as a binder resin. The first primer layer may contain fine particles.

[0035] In step S22, the optical film is melted. The optical film is melted and molded to obtain first pellets. The first pellets contain the (meth)acrylic resin and the components contained in the first primer layer.

[0036] When step S21 is performed, the crushed material is melted in step S22. The crushed material is melted and molded to obtain the first pellets. The method of melting the optical film or the method of melting the crushed material are not particularly limited, and the molding of the pellets may be performed according to a known method.

[0037] Next, in step S23, a film raw material is prepared. The film raw material includes a first pellet and a second pellet. The film raw material is obtained by mixing the first pellet and the second pellet.

[0038] The second pellets contain a (meth)acrylic resin. In addition, the second pellets are substantially free of components contained in the first primer layer. Examples of components contained in the first primer layer are resins other than (meth)acrylic resins and fine particles. In this specification, "substantially free" means that a trace amount of contamination is permitted, and the content is less than 0.1%, less than 0.01%, or even less than 0.001% by mass.

[0039] The second pellets may contain a (meth)acrylic resin as a main component. The content of the (meth)acrylic resin in the second pellets may be 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, or 99% by mass or more. The second pellets may contain only the (meth)acrylic resin.

[0040] In the film raw material, the ratio of the first pellets to the second pellets can be determined, for example, as follows. The haze value of the recycled (meth)acrylic resin film is defined as A [%]. The recycled (meth)acrylic resin film is a film formed by melting a film raw material containing the first pellets and the second pellets. On the other hand, the haze value of the reference film is defined as B [%]. The reference film is a film obtained from the second pellets and has the same thickness as the recycled (meth)acrylic resin film. That is, the reference film is a film formed by melting a film raw material containing only the second pellets. At this time, the ratio of the first pellets to the second pellets is preferably adjusted to satisfy the relationship A≦2B, that is, A / 2B≦1. This can further improve the transparency of the recycled (meth)acrylic resin film. The ratio of the first pellets to the second pellets may be adjusted to satisfy the relationship A / 2B≦0.8, or may be adjusted to satisfy the relationship A / 2B≦0.7. There is no particular limit on the lower limit of A / 2B, but it may be A / 2B≧0.5.

[0041] The ratio of the first pellets to the second pellets in the film raw material may be 1:99 to 50:50 on a mass basis, or may be 5:95 to 20:80 on a mass basis.

[0042] Next, in step S24, a recycled (meth)acrylic resin film is obtained from the film raw material. The recycled (meth)acrylic resin film is a film formed by melting the film raw material. The recycled (meth)acrylic resin film contains (meth)acrylic resin and the components contained in the first primer layer.

[0043] Thereafter, a second primer layer is laminated on the recycled (meth)acrylic resin film. This produces a recycled optical film. The method for laminating the second primer layer on the recycled (meth)acrylic resin film is as described in the first embodiment.

[0044] During steps S21 to S24, additives such as an ultraviolet absorbent and an antioxidant may be added.

[0045] Third embodiment 3 is a process diagram illustrating a method for producing a recycled (meth)acrylic resin film according to a third embodiment. In the third embodiment, the optical film is a film in which a (meth)acrylic resin film and a first primer layer are laminated. The first primer layer contains a binder resin of a different type from the (meth)acrylic resin. The first primer layer may contain fine particles.

[0046] In step S31, the first primer layer is removed from the optical film, thereby obtaining a (meth)acrylic resin film from which the first primer layer has been removed.

[0047] Methods for removing the first primer layer from the optical film include a method using a brush, a method using sandblasting, a method using sandpaper, a method using ultrasonic irradiation, a method using a hand roller, and a method in which the optical film is dissolved in a solvent and then the undissolved primer layer is removed by a filter, centrifugation, or the like. One selected from these methods may be used, or two or more may be used in combination. In step 31, only a part of the first primer layer may be removed from the optical film, or the entire first primer layer may be removed from the optical film.

[0048] The step of removing the first primer layer may be performed by a roll-to-roll method, in which the optical film is unwound from an upstream roll, the first primer layer is removed, and then the film is wound up on a downstream roll.

[0049] Next, in step S32, the (meth)acrylic resin film is crushed into chips. By crushing the (meth)acrylic resin film into chips, the raw material can be easily handled during melting. The method for crushing the (meth)acrylic resin film is the same as step S11 described in the first embodiment. Note that step S32 may be omitted.

[0050] In step S33, the (meth)acrylic resin film is melted. This makes it possible to obtain a film raw material. In particular, the (meth)acrylic resin film is melted and molded to obtain pellets as the film raw material. When step S32 is performed, crushed material of the (meth)acrylic resin film is melted in step S33. In this case, the crushed material is melted and molded to obtain pellets. The method of melting the (meth)acrylic resin film or the method of melting the crushed material are as described in the second embodiment.

[0051] The pellets obtained in step S33 contain a (meth)acrylic resin. The pellets obtained in step S33 are referred to as third pellets. The third pellets may contain a (meth)acrylic resin as a main component. The third pellets may be substantially free of components contained in the first primer layer. The third pellets may contain only a (meth)acrylic resin.

[0052] Next, in step S34, a recycled (meth)acrylic resin film is obtained from the film raw material containing the third pellets. The recycled (meth)acrylic resin film is a film formed by melting the film raw material. As described above, the third pellets are pellets obtained by reusing the optical film. According to the third embodiment, the recycled (meth)acrylic resin film can be obtained by reusing the optical film.

[0053] The film raw material may include the third pellets and pellets other than the third pellets. The pellets other than the third pellets include, for example, a (meth)acrylic resin. The pellets other than the third pellets may include a (meth)acrylic resin as a main component, or may include only a (meth)acrylic resin. Examples of the pellets other than the third pellets include pellets including the recycled (meth)acrylic resin described in the first embodiment, and the second pellets described in the second embodiment.

[0054] An example of the method for obtaining the recycled (meth)acrylic resin film from the film raw material in step S34 is as described in the second embodiment.

[0055] Thereafter, a second primer layer is laminated on the recycled (meth)acrylic resin film. This produces a recycled optical film. The method for laminating the second primer layer on the recycled (meth)acrylic resin film is as described in the first embodiment.

[0056] During steps S31 to S34, additives such as an ultraviolet absorber and an antioxidant may be added.

[0057] (Fourth embodiment) FIG. 4 is a process diagram illustrating a method for producing a recycled (meth)acrylic resin film according to a fourth embodiment. In the fourth embodiment, the optical film is a film in which a (meth)acrylic resin film and a first primer layer are laminated. The first primer layer contains a binder resin of a different type from the (meth)acrylic resin. The first primer layer may contain fine particles.

[0058] In step S41, the first primer layer is removed from the optical film. This allows a (meth)acrylic resin film from which the first primer layer has been removed from the optical film to be obtained. The method for removing the first primer layer from the optical film is as described in the third embodiment.

[0059] In step S42, the (meth)acrylic resin film is crushed into chips. By crushing the (meth)acrylic resin film into chips, it becomes easier to dissolve the crushed material in a solvent. The method for crushing the (meth)acrylic resin film is as described in the first embodiment. Note that step S42 may be omitted.

[0060] Next, in step S43, the (meth)acrylic resin film is dissolved in a solvent. This results in a solution in which the (meth)acrylic resin film is dissolved in the solvent. When step S42 is performed, in step S43, the crushed material is dissolved in a solvent. This results in a solution in which the crushed material is dissolved in the solvent.

[0061] Examples of the solvent used to dissolve the (meth)acrylic resin film and the crushed material include halogenated hydrocarbon organic solvents such as dichloromethane, ethylene chloride, and chloroform, ketone solvents such as acetone and 2-butanone, and solvents such as tetrahydrofuran, dimethylformamide, dimethylsulfoxide, and N-methyl-2-pyrrolidone. The solvent may be one selected from these solvents, or two or more of them may be used in combination.

[0062] Next, in step S44, the solution obtained in step S43 is filtered to obtain a filtrate. By filtering the solution, impurities can be removed. For example, a filter with a filtration accuracy of 0.1 to 10 μm can be used for filtration. Of course, filters with different filtration accuracy may be used in combination to perform filtration in stages.

[0063] Furthermore, in step S45, a recycled (meth)acrylic resin film is obtained from the film raw material. The film raw material contains the filtrate obtained in step S44. The filtrate contains a (meth)acrylic resin obtained by reusing an optical film. By using the filtrate, a recycled (meth)acrylic resin film can be easily formed. According to the fourth embodiment, a recycled (meth)acrylic resin film can be obtained by reusing an optical film. The film raw material may further contain a solution containing a (meth)acrylic resin. Examples of the (meth)acrylic resin contained in the solution containing a (meth)acrylic resin include a commercially available (meth)acrylic resin and the recycled (meth)acrylic resin obtained in the first embodiment.

[0064] In step S45, for example, the filtrate is applied to the surface of a substrate to form a coating film. The coating film is dried to obtain a regenerated (meth)acrylic resin film. Examples of substrates for applying the filtrate include resin films and glass plates.

[0065] Thereafter, a second primer layer is laminated on the recycled (meth)acrylic resin film. This produces a recycled optical film. The method for laminating the second primer layer on the recycled (meth)acrylic resin film is as described in the first embodiment.

[0066] During steps S41 to S45, additives such as an ultraviolet absorber and an antioxidant may be added.

[0067] Fifth embodiment The optical film according to the fifth embodiment is an optical film in which a (meth)acrylic resin film and a primer layer are laminated. In addition, the (meth)acrylic resin film contains the same type of resin as the binder resin contained in the primer layer. Here, the same type of resin as the binder resin is, for example, at least one selected from urethane resin, cellulose resin, polyol resin, polycarboxylic acid resin, and polyester resin. The (meth)acrylic resin film of this embodiment can have high transparency while containing the same type of resin as the binder resin.

[0068] FIG. 5 is a cross-sectional view showing a schematic example of an optical film. The optical film 1 includes a (meth)acrylic resin film 2 and a primer layer 3. The optical film 1 has a structure in which the primer layer 3 is formed on one main surface of the (meth)acrylic resin film 2. In FIG. 5, the primer layer 3 is formed on the entire one main surface of the (meth)acrylic resin film 2. However, the primer layer 3 may be formed only on a part of one main surface of the (meth)acrylic resin film 2. The (meth)acrylic resin film 2 is, for example, a recycled (meth)acrylic resin film obtained in the second to fourth embodiments. In this embodiment, the optical film includes a recycled (meth)acrylic resin film, so the optical film is referred to as a recycled optical film. The primer layer 3 is, for example, the second primer layer described in the first embodiment.

[0069] In the optical film of the present embodiment, a primer layer may be formed on both main surfaces of the (meth)acrylic resin film.

[0070] The (meth)acrylic resin film 2 contains a (meth)acrylic resin and a resin of the same type as the binder resin contained in the primer layer 3. The (meth)acrylic resin may contain a commercially available (meth)acrylic resin, or may contain the recycled (meth)acrylic resin described in the first embodiment. The resin of the same type as the binder resin is as exemplified above.

[0071] The (meth)acrylic resin film 2 may contain at least one component contained in the primer layer 3 at a content lower than the content in the primer layer 3. The (meth)acrylic resin film 2 may contain at least one selected from a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin in a total amount of 0.02% or less, 0.015% or less, further 0.01% or less, particularly 0.007% or less by mass. The (meth)acrylic resin film 2 may contain at least one selected from a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin in a total amount of 0.0001% or more, further 0.001% or more by mass.

[0072] The (meth)acrylic resin film 2 may further contain fine particles. The fine particles may be the same type of fine particles as the fine particles contained in the primer layer 3. The types of fine particles are as exemplified above.

[0073] The (meth)acrylic resin film 2 may further contain additives such as an ultraviolet absorber and an antioxidant.

[0074] Sixth embodiment The (meth)acrylic resin film according to the sixth embodiment contains a small amount of a resin that can function as a binder resin together with the (meth)acrylic resin. Specifically, the (meth)acrylic resin film contains a (meth)acrylic resin and at least one resin selected from a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin. In addition, the content of the at least one resin on a mass basis is 0.02% or less in total. The (meth)acrylic resin film may be a single-layer film.

[0075] The (meth)acrylic resin film may be a recycled (meth)acrylic resin film obtained by molding a recycled (meth)acrylic resin. The (meth)acrylic resin film may be obtained by melting and molding pellets obtained by melting an optical film or pellets obtained by melting a (meth)acrylic resin film. Alternatively, the (meth)acrylic resin film may be obtained by applying and drying a solution obtained by dissolving a (meth)acrylic resin film.

[0076] The (meth)acrylic resin film may contain the above resins capable of functioning as binder resins in a total amount of 0.02% or less, 0.015% or less, 0.01% or less, or even 0.007% or less by mass.The (meth)acrylic resin film may contain the above resins capable of functioning as binder resins in a total amount of 0.0001% or more, or even 0.001% or more by mass.

[0077] The second primer layer described below may contain the same type of resin as the resin contained in the (meth)acrylic resin film. This form is advantageous for realizing a (meth)acrylic resin film having high transparency.

[0078] The (meth)acrylic resin film may further contain fine particles, which may be the same type of fine particles as those contained in the second primer layer.

[0079] The (meth)acrylic resin film may further contain additives such as an ultraviolet absorber and an antioxidant.

[0080] The (meth)acrylic resin film has a high total light transmittance. The total light transmittance of the (meth)acrylic resin film may be 90% or more, 91% or more, or 92% or more. The upper limit of the total light transmittance is, for example, 99%.

[0081] The (meth)acrylic resin film has a low haze value. The haze value of the (meth)acrylic resin film may be 1.0% or less, 0.9% or less, 0.7% or less, or 0.5% or less. The lower limit of the haze value is, for example, 0%.

[0082] The (meth)acrylic resin film has a low yellowness index (YI value). The YI value of the (meth)acrylic resin film may be 0.4 or less, 0.3 or less, or 0.2 or less. The lower limit of the YI value is, for example, zero.

[0083] The (meth)acrylic resin film may contain at least one selected from urethane resin, cellulose resin, polyol resin, polycarboxylic acid resin, and polyester resin only in the thickness direction. In other words, at least one selected from urethane resin, cellulose resin, polyol resin, polycarboxylic acid resin, and polyester resin may not be exposed on the main surface of the (meth)acrylic resin film. This allows the (meth)acrylic resin film to suppress light scattering on the surface.

[0084] FIG. 6 is a cross-sectional view showing another example of a (meth)acrylic resin film. The (meth)acrylic resin film 2a includes a first layer 4 and a second layer 5. In the (meth)acrylic resin film 2a, the second layer 5 is laminated to the first layer 4. The first layer 4 is a (meth)acrylic resin film according to the sixth embodiment. The first layer 4 is not exposed on the main surface of the (meth)acrylic resin film 2a. That is, the second layer 5 is formed on the entirety of one main surface of the first layer 4. The first layer 4 contains a (meth)acrylic resin and a resin other than the (meth)acrylic resin. Examples of the resin other than the (meth)acrylic resin include a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin. The first layer 4 may contain at least one selected from a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin. The second layer 5 contains a (meth)acrylic resin. The second layer 5 may not substantially contain a resin other than the (meth)acrylic resin.

[0085] The (meth)acrylic resin film 2a may further include a third layer 6 laminated on the first layer 4. The first layer 4 is disposed between the second layer 5 and the third layer 6. The third layer 6 may be formed on the entire main surface of the first layer 4. The composition of the resin contained in the third layer 6 may be the same as the composition of the resin contained in the second layer 5. The third layer 6 may be substantially free of resins other than the (meth)acrylic resin. As a result, the (meth)acrylic resin film 2a contains at least one selected from a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin only inside in the thickness direction.

[0086] In the (meth)acrylic resin film 2a, the thickness of the first layer 4 may be 1 to 30 μm, or may be 5 to 20 μm. By appropriately adjusting the thickness of the first layer 4, the transparency of the (meth)acrylic resin film is further improved.

[0087] In the (meth)acrylic resin film 2a, the second layer 5 may have a thickness greater than that of the first layer 4. The second layer 5 may have a thickness of 5 to 50 μm, or 12 to 35 μm. The third layer 6 may have a thickness equal to that of the second layer 5. By appropriately adjusting the thicknesses of the second layer 5 and the third layer 6, the strength and transparency of the (meth)acrylic resin film 2a are further improved.

[0088] A primer layer may be formed on a portion of one of the main surfaces of the (meth)acrylic resin film 2a. This primer layer is referred to as a second primer layer. In the (meth)acrylic resin film 2a, the second primer layer may be formed on the entire main surface of the second layer 5. The second primer layer may be formed only on a portion of the main surface of the second layer 5.

[0089] The second primer layer is, for example, the primer layer 3 described in the fifth embodiment. The second primer layer contains a binder resin. The second primer layer may further contain fine particles. The binder resin contained in the second primer layer may be the same type of resin as the binder resin contained in the first layer 4. When the second primer layer contains fine particles, the fine particles contained in the second primer layer may be the same type of fine particles as the fine particles contained in the first layer 4.

[0090] In the (meth)acrylic resin film 2a, a primer layer may be formed on the third layer 6. A primer layer may be formed on the entire main surface of the third layer 6. A primer layer may be formed on only a part of the main surface of the third layer 6. When primer layers are formed on the second layer 5 and the third layer 6, the composition of the resin contained in the primer layer formed on the second layer 5 may be the same as the composition of the resin contained in the primer layer formed on the third layer 6. The primer layer may further contain fine particles.

[0091] [Recycled (meth)acrylic resin film] Hereinafter, the recycled (meth)acrylic resin film obtained from each of the above-mentioned embodiments will be described. The recycled (meth)acrylic resin film means a (meth)acrylic resin film obtained by reusing an optical film. The recycled (meth)acrylic resin film is obtained, for example, by molding a recycled (meth)acrylic resin. The recycled (meth)acrylic resin film may be obtained by melting and molding pellets obtained by melting an optical film or pellets obtained by melting a (meth)acrylic resin film. Alternatively, the recycled (meth)acrylic resin film may be obtained by applying and drying a solution obtained by dissolving a (meth)acrylic resin film.

[0092] The recycled (meth)acrylic resin film contains a (meth)acrylic polymer. The (meth)acrylic polymer is a polymer having a structural unit derived from a (meth)acrylic acid ester monomer. In this specification, the structural unit derived from a (meth)acrylic acid ester monomer is referred to as a (meth)acrylic acid ester unit. The content of the (meth)acrylic acid ester unit in the (meth)acrylic polymer may be 10% by weight or more, 30% by weight or more, 50% by weight or more, or 70% by weight or more. The weight average molecular weight of the (meth)acrylic polymer may be 10,000 to 500,000, or 50,000 to 300,000.

[0093] The (meth)acrylic acid ester unit is, for example, a structural unit derived from each monomer of methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, chloromethyl (meth)acrylate, 2-chloroethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2,3,4,5,6-pentahydroxyhexyl (meth)acrylate, and 2,3,4,5-tetrahydroxypentyl (meth)acrylate. The optical properties and thermal stability of the finally obtained recycled optical film are improved by the (meth)acrylic polymer having a structural unit derived from methyl (meth)acrylate. The (meth)acrylic polymer may have two or more (meth)acrylic acid ester units.

[0094] The (meth)acrylic polymer may have a structural unit other than the (meth)acrylic acid ester unit. Such a structural unit is, for example, a structural unit derived from each monomer of styrene, vinyltoluene, α-methylstyrene, α-hydroxymethylstyrene, α-hydroxyethylstyrene, acrylonitrile, methacrylonitrile, ethylene, propylene, 4-methyl-1-pentene, vinyl acetate, 2-hydroxymethyl-1-butene, methyl vinyl ketone, N-vinylpyrrolidone, and N-vinylcarbazole. The (meth)acrylic polymer may have two or more of these structural units.

[0095] The (meth)acrylic polymer may have a ring structure in the main chain. Such a (meth)acrylic polymer is obtained by copolymerizing a (meth)acrylic acid ester monomer with a monomer having a ring structure. Alternatively, the (meth)acrylic polymer is obtained by polymerizing a monomer group including a (meth)acrylic acid ester monomer and then carrying out a cyclization reaction. When the (meth)acrylic polymer has a ring structure in the main chain, the total content of the (meth)acrylic acid ester unit and the ring structure may be 50% by weight or more.

[0096] The ring structure is, for example, at least one selected from an N-substituted maleimide structure, a maleic anhydride structure, a glutarimide structure, a glutaric anhydride structure, and a lactone ring structure. The N-substituted maleimide structure is, for example, a cyclohexylmaleimide structure, a methylmaleimide structure, a phenylmaleimide structure, and a benzylmaleimide structure. From the viewpoint of the heat resistance of the optical film, the ring structure is preferably a lactone ring structure, a cyclic imide structure (for example, an N-alkyl-substituted maleimide structure, a glutarimide structure), or a cyclic anhydride structure (for example, a maleic anhydride structure and a glutaric anhydride structure). The ring structure may include a glutarimide structure, a glutaric anhydride structure, a lactone ring structure, a maleic anhydride structure, and an N-substituted maleimide structure.

[0097] The glutaric anhydride structure and the glutarimide structure are shown in the following general formula (1).

[0098] [ka]

[0099] R in general formula (1) 1 , R 2 are each independently a hydrogen atom or a methyl group, and X 1 is an oxygen atom or a nitrogen atom. X 1 is an oxygen atom, R 3 does not exist. X 1 is a nitrogen atom, R 3 is a hydrogen atom, a linear alkyl group having 1 to 6 carbon atoms, a cyclopentyl group, a cyclohexyl group, a benzyl group, or a phenyl group.

[0100] X 1 When X is an oxygen atom, the ring structure represented by the general formula (1) is a glutaric anhydride structure. The glutaric anhydride structure can be formed, for example, by intramolecular dealcoholization cyclocondensation of a copolymer of a (meth)acrylic acid ester and (meth)acrylic acid. 1When is a nitrogen atom, the ring structure represented by the general formula (1) is a glutarimide structure. The glutarimide structure can be formed, for example, by imidizing a (meth)acrylic acid ester polymer with an imidizing agent such as methylamine.

[0101] The maleic anhydride structure and the N-substituted maleimide structure are shown in the following general formula (2).

[0102] [ka]

[0103] R in general formula (2) 4 , R 5 are each independently a hydrogen atom or a methyl group, and X 2 is an oxygen atom or a nitrogen atom. X 2 is an oxygen atom, R 6 does not exist. X 2 is a nitrogen atom, R 6 is a hydrogen atom, a linear alkyl group having 1 to 6 carbon atoms, a cyclopentyl group, a cyclohexyl group, a benzyl group, or a phenyl group.

[0104] X 2 When X is an oxygen atom, the ring structure represented by the general formula (2) is a maleic anhydride structure. The maleic anhydride structure can be formed, for example, by copolymerizing maleic anhydride with a (meth)acrylic acid ester. 2 When is a nitrogen atom, the ring structure represented by general formula (2) is an N-substituted maleimide structure.

[0105] In the methods for forming the ring structures exemplified in the description of general formulas (1) and (2), all of the polymers used for forming the respective ring structures have (meth)acrylic acid ester units as constituent units, and therefore the resulting resin is a (meth)acrylic resin.

[0106] The lactone ring structure is shown in the following general formula (3).

[0107] [ka]

[0108] In the general formula (3), R 7 , R 8 and R 9 are each independently a hydrogen atom or an organic residue having 1 to 20 carbon atoms. The organic residue may contain an oxygen atom.

[0109] Examples of the organic residue in the general formula (3) include an alkyl group, an unsaturated aliphatic hydrocarbon group, and an aromatic hydrocarbon group. The number of carbon atoms in the alkyl group is, for example, 1 to 20. Examples of the alkyl group include a methyl group, an ethyl group, and a propyl group. The number of carbon atoms in the unsaturated aliphatic hydrocarbon group is, for example, 2 to 20. Examples of the unsaturated aliphatic hydrocarbon group include an ethenyl group and a propenyl group. The number of carbon atoms in the aromatic hydrocarbon group is, for example, 6 to 20. Examples of the aromatic hydrocarbon group include a phenyl group and a naphthyl group. In the alkyl group, the unsaturated aliphatic hydrocarbon group, and the aromatic hydrocarbon group, one or more hydrogen atoms may be substituted with at least one group selected from a hydroxyl group, a carboxyl group, an ether group, and an ester group.

[0110] General formula (3) shows a 6-membered lactone ring structure. The lactone ring structure may be a 4- to 8-membered ring. The ring structure may be a 5- or 6-membered ring because of its excellent stability.

[0111] Another lactone ring structure (a structural unit derived from α-methylene lactone) is shown in the following general formula (4).

[0112] [ka]

[0113] In the general formula (4), R 10 ~R 13 are each independently a hydrogen atom or a hydrocarbon group having 1 to 18 carbon atoms.

[0114] A constitutional unit having the structure shown in formula (4) can be formed by polymerization of a monomer containing α-methylene-γ-butyrolactone shown in the following formula (5).

[0115] [ka]

[0116] R in general formula (5) 10 ~R 13 are each independently a hydrogen atom or a hydrocarbon group having 1 to 18 carbon atoms. The hydrocarbon group is an aliphatic hydrocarbon group or an aromatic hydrocarbon group. The aliphatic hydrocarbon group is, for example, an alkyl group. The number of carbon atoms in the alkyl group is preferably 1 to 10, more preferably 1 to 8. The alkyl group may be linear or branched, or may be cyclic. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, a t-butyl group, an n-pentyl group, an n-hexyl group, a cyclopentyl group, and a cyclohexyl group. The aromatic hydrocarbon group is not particularly limited, and may include, for example, a heterocyclic structure. Examples of the aromatic hydrocarbon group include a phenyl group, a tolyl group, and a benzyl group. R 10 ~R 13 are preferably each independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and more preferably all are a hydrogen atom.

[0117] When the (meth)acrylic polymer has a ring structure in the main chain, the content of the ring structure in the polymer may be 5 to 90% by weight, 10 to 70% by weight, 10 to 60% by weight, or 10 to 50% by weight. When the content of the ring structure is 5% by weight or more, the heat resistance, solvent resistance, and surface hardness of the film are particularly excellent. When the content of the ring structure is 90% by weight or less, the ease of stretching the recycled (meth)acrylic resin film and the handleability during production of the recycled (meth)acrylic resin film are particularly excellent. The content of each constitutional unit in the copolymer is determined by dissolving the copolymer in a heavy solvent and 1It can be determined by measuring H-NMR and calculating the area ratio of the peaks corresponding to each structural unit.

[0118] The Tg (glass transition temperature) of the recycled (meth)acrylic resin may be 100° C. or higher, 110° C. or higher, 115° C. or higher, or 120° C. or higher. The upper limit of the Tg of the recycled (meth)acrylic resin may be 170° C., from the viewpoint of stretchability when made into a recycled (meth)acrylic resin film.

[0119] The recycled (meth)acrylic resin film is obtained by molding recycled (meth)acrylic resin. The thickness of the recycled (meth)acrylic resin film may be 5 to 200 μm, 5 to 100 μm, or 25 to 50 μm. When the thickness is 5 μm or more, the strength is excellent. When the thickness is 200 μm or less, the transparency is excellent.

[0120] [Primer layer] The recycled optical film has a primer layer formed on the surface of a recycled (meth)acrylic resin film. The recycled optical film means an optical film manufactured using a recycled (meth)acrylic resin film. The primer layer of the recycled optical film is called a second primer layer. The second primer layer contains a binder resin. The second primer layer may contain a binder resin as a main component. The binder resin may be any of the resins exemplified above.

[0121] The second primer layer may contain a urethane resin, which improves the adhesion of the second primer layer to the recycled (meth)acrylic resin film and also improves the adhesion of the recycled optical film.

[0122] The second primer layer may further contain fine particles. The types of the fine particles are as described above.

[0123] The particle size of the fine particles is not particularly limited, but is 1000 nm or less, for example, 10 to 500 nm. EXAMPLES

[0124] First, the methods for evaluating the recycled (meth)acrylic resin and (meth)acrylic resin film produced in this example will be described.

[0125] (1) Number average molecular weight (Mn), weight average molecular weight (Mw) The number average molecular weight and the weight average molecular weight were determined in terms of polystyrene using gel permeation chromatography (GPC) using the following apparatus and conditions:

[0126] -System: Tosoh GPC system HLC-8220 - Measurement column configuration Guard column: Tosoh Corporation, TSKguardcolumn SuperHZ-L Separation column: Tosoh Corporation, TSKgel SuperHZM-M, 2 columns connected in series -Reference column configuration Reference column: Tosoh Corporation, TSKgel SuperH-RC -Developing solvent: Chloroform (Wako Pure Chemical Industries, special grade) -Flow rate of developing solvent: 0.6mL / min -Standard sample: TSK standard polystyrene (Tosoh Corporation, PS-oligomer kit) -Column temperature: 40℃

[0127] (2) Glass transition temperature (Tg) The glass transition temperature was determined in accordance with the provisions of Japanese Industrial Standards (JIS) K 7121. A differential scanning calorimeter (DSC) (Rigaku Thermo plus EVO DSC-8230) was used for the analysis. The evaluation was performed by the starting point method from the DSC curve obtained by heating about 10 mg of a sample from room temperature to 200°C under a nitrogen gas atmosphere. The heating rate was 20°C / min. α-alumina was used as a reference.

[0128] (3) Thermal decomposition start temperature The thermal decomposition onset temperature of the resin was measured using a differential thermogravimetry analyzer (Shimadzu Corporation, DTG-50) in accordance with the provisions of JIS K 7120. The thermal decomposition onset temperature is the temperature at which the mass of the resin starts to decrease in thermogravimetry. The measurement was performed under conditions of a temperature rise rate of 10°C / min and a nitrogen flow of 50 mL / min as the inflow gas.

[0129] (4) Film thickness The thickness of the film was measured using a Digimatic Micrometer (manufactured by Mitutoyo Corporation).

[0130] (5) Total light transmittance, haze value The total light transmittance and haze value of the film were measured using a turbidity meter (NDH5000, manufactured by Nippon Denshoku Industries Co., Ltd.).

[0131] (6) YI value (yellowness index) The YI value of the film was measured using a colorimeter (Color meter ZE6000, manufactured by Nippon Denshoku Industries Co., Ltd.).

[0132] (7) Refractive index The refractive index of the film was measured using an Abbe refractometer (Abbe refractometer 2-T, manufactured by Atago Co., Ltd.).

[0133] (8) Relationship between the amount of first pellets used in (meth)acrylic resin film and the haze value of the film The haze value of the (meth)acrylic resin film of each sample is defined as A [%]. Meanwhile, the haze value of the reference film is defined as B [%]. The reference film is a film obtained by melting and molding the pellets obtained in sample 1-1. At this time, A / 2B was calculated. In the measurement of the haze value, the thickness of the (meth)acrylic resin film and the thickness of the reference film were the same. In samples 21 to 26, the pressed film of sample X2 was used as the reference film. In samples 31 and 32, the melt-extruded film of sample X3 was used as the reference film.

[0134] (9) Measurement of primer layer thickness The thickness of the primer layer was measured by one of the following two methods. Note that the thickness of the primer layer was the same regardless of the method.

[0135] (9-1) Measurement by SEM The cross section of the optical film in which the primer layer was laminated on the (meth)acrylic resin film was observed using a scanning electron microscope (FE-SEM S-4800, manufactured by Hitachi High-Technologies Corporation) to measure the thickness of the primer layer. The measurement conditions were as follows.

[0136] [Measurement conditions] Accelerating voltage: 20 kV Emission current: 5μA or 10μA Working distance (WD): 8mm

[0137] (9-2) Measurement by FT-IR The IR spectrum of the optical film was measured using FT-IR (iS10, manufactured by ThermoSCIENTIFIC). The peak intensity ratio (b / a) between the peak (a) attributable to the base film ((meth)acrylic resin film) and the peak (b) attributable to the primer layer was calculated. The peak intensity ratio (b / a) was converted to the thickness of the primer layer by referring to the conversion formula of the thickness of the primer layer to the peak intensity ratio obtained by the method shown below.

[0138] The conversion formula for the thickness of the primer layer to the peak intensity ratio was determined by the following method. The peak intensity ratio (b / a) was calculated for an optical film with a known thickness of the base film and primer layer. Separately, the peak intensity ratio (b / a) was calculated for a film without a primer layer and with a known thickness of the base film. A linear approximation line was obtained from the ratio of the two peak intensities. The formula for this approximation line was defined as the conversion formula for the thickness of the primer layer to the peak intensity ratio. The FT-IR measurement conditions were as follows:

[0139] [Measurement conditions] Measurement method: ATR method Measurement area: 650-4000cm -1 Resolution: 4cm -1 Number of times: 32

[0140] (10) Measurement of the amount of urethane resin contained in the film For an optical film having no primer layer on at least one side, an IR spectrum was measured from the side having no primer layer. From this, the peak intensity ratio (b / a) between the peak (a) attributable to the base film and the peak (b) attributable to a substance (urethane resin) derived from the primer layer contained in the base film was calculated. By comparing this with the content-peak intensity ratio conversion formula obtained by the method shown below, the peak intensity ratio (b / a) was converted into the content of urethane resin.

[0141] The conversion formula of content-peak intensity ratio was obtained by the following method. For an optical film with known thicknesses of the base film and primer layer, the value of (thickness of primer layer) / (thickness of base film) was defined as the content of urethane resin. Then, this optical film was crushed into a square with a side of about 5 mm and melted. The pellets thus obtained were pressed to produce a film. The IR spectrum of the obtained film was measured. As a result, the peak intensity ratio (b / a) of the peak (a) belonging to the base film and the peak (b) belonging to the urethane resin was calculated. Separately, the peak intensity ratio (b / a) was calculated by the above-mentioned method for an optical film that does not contain a urethane resin in the base film. A linear approximation line was obtained from the value of the ratio of the two peak intensities. The formula of this approximation line is defined as the conversion formula of content-peak intensity ratio. The measurement conditions of FT-IR are as described in (9-2).

[0142] In addition, when the optical film had a primer layer on both sides, the primer layer on one side was removed before the above measurement. In addition, when the film was a laminated film, the film was once crushed, the crushed material was melted, and the pellets were molded, and the above measurement was performed on the film obtained by melt press molding.

[0143] (Sample 1-1) In a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen inlet tube, 229.6 parts of commercially available methyl methacrylate (MMA), 33 parts of 2-(hydroxymethyl)methyl acrylate (MHMA), 0.138 parts of an antioxidant (ADEKA Corporation's "Adekastab 2112"), 248.6 parts of toluene as a non-polymerizable organic solvent, and 0.1925 parts of n-dodecyl mercaptan were added, and the temperature was raised to 105°C while nitrogen was passed through the reaction vessel. When refluxing with the temperature increase began, 0.2838 parts of t-amyl peroxy isononanoate (Arkema Yoshitomi Corporation's "Luperox 570") was added as a polymerization initiator, and 0.5646 parts of the above t-amyl peroxy isononanoate and 12.375 parts of styrene (St) were added dropwise over 2 hours to allow solution polymerization to proceed under reflux at about 105 to 110°C. After the dropwise addition, the mixture was aged for an additional 4 hours at about 105-110°C. "ADEKA STAB" is a registered trademark of ADEKA Corporation. "LUPEROX" is a registered trademark of ARKEMA Corporation.

[0144] Next, 0.206 parts of stearyl phosphate ("Phoslex A-18" manufactured by Sakai Chemical Industry Co., Ltd.) was added as a catalyst for the cyclization condensation reaction (cyclization catalyst) to the obtained polymerization solution, and the cyclization condensation reaction for forming a lactone ring structure was allowed to proceed under reflux at approximately 90 to 110°C for 2 hours.

[0145] Next, the obtained polymerization solution was passed through a multi-tube heat exchanger heated to 240°C to complete the cyclization condensation reaction. After that, the solution after the reaction was introduced into a vent-type screw twin-screw extruder at a processing rate of 31.2 parts / hour in terms of the amount of resin, and devolatilization was carried out. During devolatilization, ion-exchanged water was fed from behind the second vent and behind the fourth vent at a feeding rate of 0.47 parts / hour. In addition, a toluene solution of zinc octylate (Nihon Kagaku Sangyo Co., Ltd.'s "Nikka Octix Zinc 18%"), 50 parts of Irganox 1010 (Ciba Specialty Chemicals Co., Ltd.), and Adeka STAB AO-412S (ADEKA Corporation) was injected so that the mass ratio of zinc octylate was 160 ppm, Irganox 1010 was 50 ppm, and Adeka STAB AO-412S was 50 ppm relative to the obtained thermoplastic resin composition.

[0146] The vent-type twin-screw extruder had one rear vent and four fore vents under the condition of a barrel temperature of 250°C. The four fore vents are called the first fore vent, the second fore vent, the third fore vent, and the fourth fore vent from the upstream side. In addition, the vent-type twin-screw extruder had a side feeder between the third and fourth vents. Furthermore, a leaf disk-type polymer filter was placed at the tip of the vent-type twin-screw extruder. The filtration accuracy of the polymer filter was 5 μm. The degree of vacuum of the rear vent was set to 798 hPa. The degree of vacuum of the first vent was set to 266 hPa. The degrees of vacuum of the second vent to the fourth vent were all set to 27 hPa.

[0147] After the devolatilization was completed, the resin composition in a molten state remaining in the extruder was discharged from the tip of the extruder while being filtered with the above-mentioned polymer filter. After passing through a die, it was filtered with a filter having a pore size of 1 μm (product name: Micropore Filter 1EU, manufactured by Organo Corporation), and the strand was cooled in a water tank filled with cooling water maintained at a temperature within the range of 30±10° C. Next, the strand was introduced into a cutting machine (pelletizer) to obtain pellets (1C) made of a resin composition (1A) containing a lactone ring polymer having a lactone ring structure in the main chain.

[0148] (Sample 1-2) As the resin composition (2A), a commercially available polymethyl methacrylate (PMMA) resin (manufactured by Sumitomo Chemical Co., Ltd., trade name: Sumipex EX) was used.

[0149] (Sample 1-3) An acrylic resin (product name: Pleximide 8813) manufactured by Daicel-Evonik was used as the resin composition (3A). This acrylic resin contains as its main component a (meth)acrylic polymer having a glutarimide structure in the main chain. A part of the monomers constituting this polymer is methyl methacrylate.

[0150] (Sample 1-4) An acrylic resin (product name: Polyimilex PML203) manufactured by Nippon Shokubai Co., Ltd. was used as the resin composition (4A). This acrylic resin contains, as a main component, a (meth)acrylic polymer having a maleimide structure in the main chain. A part of the monomer constituting this polymer is methyl methacrylate.

[0151] (Sample 2-1) 0.09 parts by weight of an emulsion containing amorphous silica fine particles (Seahoster KE-W30, manufactured by Nippon Shokubai Co., Ltd., average particle size (primary particle size) 0.28 μm, particle size distribution 1.1, solid content 20% by weight) and 20 parts by weight of a urethane resin (Superflex 210, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., solid content 35% by weight) were added in this order to 80 parts by weight of stirred pure water and mixed thoroughly to obtain a mixed liquid. This mixed liquid was then passed through a filter with a pore size of 1 μm to obtain a primer composition (1B) which is an emulsion-like dispersion.

[0152] (Sample 3-1) Pellets (1C) made of the resin composition (1A) were dried in a hot air oven at 80°C for 8 hours. Thereafter, the pellets (1C) were melt-pressed at 230°C for 2 minutes using a manual heating press (IMC-180C, manufactured by Imoto Manufacturing Co., Ltd.) to obtain a (meth)acrylic resin film (1P). The (meth)acrylic resin film according to Sample 3-1 was a pressed film. The thickness of the pressed film (1P) according to Sample 3-1 was 150±10 μm.

[0153] (Sample 4-1) Pellets (1C) made of the resin composition (1A) were dried in a hot air oven at 80°C for 8 hours. Thereafter, the pellets (1C) were melt-extruded from a coat hanger type T-die with a width of 150 mm at 270°C using a twin-screw extruder to obtain a (meth)acrylic resin film (1M). The (meth)acrylic resin film according to Sample 4-1 was a melt-extruded film. The thickness of the melt-extruded film according to Sample 4-1 was about 100 μm. The twin-screw extruder had a screw with a diameter of 20 mm. During melt extrusion, the optical film was discharged from the T-die onto a cooling roll maintained at 110°C, and then taken up by a winder after passing through multiple rolls.

[0154] (Sample 4-2) A (meth)acrylic resin film (4M) was obtained in the same manner as in Sample 4-1, except that pellets (4C) made of the resin composition (4A) were used and melt extrusion was performed at 250° C. The (meth)acrylic resin film of Sample 4-2 was a melt-extruded film.

[0155] (Sample 5-1) Pellets (1C) made of the resin composition (1A) were dried in a hot air oven at 80°C for 8 hours. The pellets (1C) were then melt-extruded from a T-die at 280°C using a single-screw extruder equipped with a polymer filter at the tip. The filtration accuracy of the polymer filter was 5 μm. The resulting film was then extruded onto a cooling roll at 110°C to form a film. The thickness of the formed film was 174 μm.

[0156] Next, the formed film was continuously fed to an oven longitudinal stretching machine following melt extrusion, and the film was uniaxially stretched at a free end in the longitudinal direction of the film at a stretching temperature of 136°C and a stretching ratio of 2.2 times in the stretching machine. The longitudinal direction of the film is the flow direction during melt extrusion, which is the MD direction. This resulted in a longitudinally stretched film. The longitudinally stretched film was then wound into a roll. The thickness of the longitudinally stretched film was 116 μm.

[0157] Next, the primer composition (1B) was applied to one side of the longitudinally stretched film by gravure coating so that the thickness of the coating film after drying was 1200 nm. Then, the longitudinally stretched film was gripped at positions 20 mm from both ends with 2-inch clips and fed to a tenter stretching machine, and transversely stretched under conditions of a stretching temperature of 143°C and a stretching ratio of 3.0 times. In this way, an optical film (1F) was obtained, which is a biaxially stretched film having a primer layer formed on one main surface. Then, the optical film (1F) was wound into a roll. The thickness of the optical film (1F) was 40 μm. The thickness of the primer layer was 400 nm.

[0158] (Sample 5-2) Except for using the pellets (2C) made of the resin composition (2A), the same method as in sample 5-1 was used to obtain an optical film (2F). The thickness of the optical film (2F) was 40 μm. The thickness of the primer layer was 400 nm.

[0159] (Sample 5-3) Except for using the pellets (3C) made of the resin composition (3A), the same method as in sample 5-1 was used to obtain an optical film (3F). The thickness of the optical film (3F) was 40 μm. The thickness of the primer layer was 400 nm.

[0160] [Production of recycled (meth)acrylic resin using MMA obtained by depolymerization] (Sample 1) Optical film (1F) was used as the raw material. The optical film (1F) was crushed and added to the reaction vessel. The reaction vessel was heated to 380°C to depolymerize the optical film (1F) and recover the volatile components. The volatile components included methyl methacrylate and styrene. The recovered volatile components were then purified by distillation under atmospheric pressure to obtain regenerated methyl methacrylate (MMA).

[0161] Next, pellets (1C-1) made of a resin composition (1A-1) containing a lactone ring polymer having a lactone ring structure in the main chain were obtained in the same manner as in Sample 1-1, except that recycled methyl methacrylate was used instead of commercially available methyl methacrylate. The number average molecular weight, weight average molecular weight, glass transition temperature, thermal decomposition onset temperature, and refractive index of the obtained resin composition (1A-1) were measured. The results are shown in Table 1.

[0162] (Sample 2) Recycled methyl methacrylate for Sample 2 was obtained in the same manner as Sample 1, except that a mixture of optical film (1F), optical film (2F), and optical film (3F) mixed in a weight ratio of 1:1:1 was used as a raw material. Next, pellets (1C-2) made of a resin composition (1A-2) containing a lactone ring polymer having a lactone ring structure in the main chain were obtained in the same manner as Sample 1-1, except that this recycled methyl methacrylate was used.

[0163] (Sample X1) The resin composition (1A) prepared in Sample 1-1 was used.

[0164] [Table 1]

[0165] As shown in Table 1, in Samples 1 and 2, the physical properties of the resin compositions were the same as those of the resin composition of Sample X1.

[0166] [Production of press film using MMA obtained by depolymerization] (Sample 11) A (meth)acrylic resin film (1P-1) was obtained in the same manner as in Sample 3-1, except that the pellets (1C-1) were used. The (meth)acrylic resin film according to Sample 11 was a pressed film. The total light transmittance, haze value, YI, and urethane resin content of the pressed film (1P-1) according to Sample 11 were measured. The results are shown in Table 2.

[0167] (Sample 12) A pressed film (1P-2) was produced in the same manner as in Sample 3-1, except that the pellets (1C-2) were used.

[0168] (Sample X2) The pressed film (1P) prepared in Sample 3-1 was used.

[0169] [Table 2]

[0170] As shown in Table 2, in Samples 11 and 12, the physical properties of the pressed films obtained using recycled methyl methacrylate were comparable to those of the pressed film produced in Sample X2.

[0171] [Production of melt-extruded film using MMA obtained by depolymerization] (Sample 13) A (meth)acrylic resin film (1M-1) was obtained in the same manner as in Sample 4-1, except that the pellets (1C-1) were used. The (meth)acrylic resin film of Sample 13 was a melt-extruded film. The melt-extruded film (1M-1) of Sample 13 was measured for total light transmittance, haze value, YI, and urethane resin content. The results are shown in Table 3.

[0172] (Sample 14) A melt-extruded film (1M-2) of Sample 14 was obtained in the same manner as Sample 4-1, except that the pellets (1C-2) were used.

[0173] (Sample 15) Recycled methyl methacrylate for sample 15 was obtained in the same manner as sample 1, except that a mixture of optical film (1F), optical film (2F), and optical film (3F) in a weight ratio of 1:1:1 was used as the raw material.

[0174] Next, 30 parts by weight of the regenerated methyl methacrylate of Sample 15, 0.05 parts by weight of an antioxidant (ADEKA Corporation, Adekastab 2112), and 65 parts by weight of methyl ethyl ketone (MEK) as a polymerization solvent were added to a reaction vessel. The internal temperature was raised to 80°C while introducing nitrogen gas into the reaction vessel, and when reflux began, 0.052 parts by weight of t-amylperoxy-2-ethylhexanoate (Arkema Yoshitomi Corporation, Luperox 575) as a polymerization initiator and 5 parts by weight of MEK were added to prepare a reaction solution. After the addition, the reaction solution was stirred for 6 hours under reflux under a nitrogen stream to obtain a polymerization solution.

[0175] Next, the obtained polymerization solution was added to a vent-type twin screw extruder. The volatile matter was removed under the condition of a barrel temperature of 240°C, and pellets were prepared from the polymer contained in the polymerization solution. As a result, pellets (1C-3) made of a transparent resin composition (5A-2) which is polymethyl methacrylate (PMMA) were obtained. The weight average molecular weight of the obtained resin composition (5A-2) was 100,000, and the glass transition temperature was 97°C.

[0176] Except for using the obtained pellets (1C-3), the same method as for Sample 4-1 was used to obtain a (meth)acrylic resin film (5M-2) according to Sample 15. The (meth)acrylic resin film according to Sample 15 was a melt-extruded film.

[0177] (Sample X3) The melt-extruded film (1M) produced in Sample 4-1 was used.

[0178] (Sample X4) The melt-extruded film (4M) produced in Sample 4-2 was used.

[0179] [Table 3]

[0180] As shown in Table 3, in samples 13 to 15, the physical properties of the melt-extruded films obtained using recycled methyl methacrylate were comparable to those of the melt-extruded film of sample X3 and the melt-extruded film of sample X4.

[0181] [Mixing the first and second pellets and producing a press film] (Sample 21) Pellets (1C) made of the resin composition (1A) and pellets (1D) obtained from the optical film (1F) were mixed in the mass ratio shown in Table 4, and then melted at 280°C and molded to obtain a mixture. The optical film (1F) was crushed into squares, and then melted and molded to obtain pellets (1D). Next, a (meth)acrylic resin film according to Sample 21 was obtained in the same manner as Sample 3-1, except that the obtained mixture was used. The (meth)acrylic resin film according to Sample 21 was a pressed film. The thickness of the pressed film according to Sample 21 was 150±10 μm. The total light transmittance, haze value, YI, and urethane resin content of the pressed film according to Sample 21 were measured. The results are shown in Table 4.

[0182] (Samples 22-26) The (meth)acrylic resin films according to Samples 22 to 26 were obtained in the same manner as Sample 21, except that the pellets (1C) and the pellets (1D) were mixed in the mass ratio shown in Table 4 to obtain a mixture. The (meth)acrylic resin films according to Samples 22 to 26 were pressed films. The thickness of the obtained (meth)acrylic resin films was 150±10 μm.

[0183] (Sample X2) The pressed film (1P) prepared in Sample 3-1 was used.

[0184] [Table 4]

[0185] As shown in Table 4, the physical properties of the pressed films of Samples 21 to 26 were comparable to those of the pressed film of Sample X2. In the pressed films of Samples 21 to 23, the urethane resin content was 0.02 mass% or less, and the relationship A / 2B≦1 was satisfied. In the pressed films of Samples 24 to 26, the total light transmittance, haze value, and YI were inferior to those of the pressed film of Sample X2. In the pressed films of Samples 24 to 26, the urethane resin content was more than 0.02 mass%, and the relationship A / 2B≦1 was not satisfied. In Samples 21 to 23, the total light transmittance, haze value, and YI were superior to those of Samples 24 to 26.

[0186] [Mixing of the first pellet with the second pellet and preparation of a melt extrusion film] (Samples 31 and 32) Pellet (1C) and pellet (1D) were mixed in the mass ratio shown in Table 5 to obtain a mixed pellet. A melt-extruded film was obtained in the same manner as Sample 4-1, except that this mixed pellet was used. The thickness of the melt-extruded film was 150±10 μm.

[0187] (Sample X3) The melt-extruded film (1M) produced in Sample 4-1 was used.

[0188] [Table 5]

[0189] As shown in Table 5, the physical properties of the melt-extruded films of Samples 31 and 32 were comparable to those of the melt-extruded film of Sample X3. In the melt-extruded film of Sample 31, the content of the urethane resin was 0.02 mass%, and the relationship A / 2B≦1 was satisfied. In the melt-extruded film of Sample 32, the haze value was inferior to that of the melt-extruded film of Sample X3. In the melt-extruded film of Sample 32, the content of the urethane resin was more than 0.02 mass%, and the relationship A / 2B≦1 was not satisfied. In Sample 31, the total light transmittance, haze value, and YI were superior to those of Sample 32.

[0190] [Laminated film] (Samples 41 and 42) Pellets (1C) were added to the single screw extruder A. Meanwhile, pellets (1D) were added to the single screw extruder B. A laminate was obtained through a feed block so that a layer structure was formed in the order of a layer (second layer) made of pellets (1C) / a layer (first layer) made of pellets (1D) / a layer (third layer) made of pellets (1C). Next, this laminate was extruded into a sheet shape using a coat hanger type T die having a width of 150 mm to obtain a (meth)acrylic resin film. This (meth)acrylic resin film was a melt extruded film. The thickness of this melt extruded film was 100 μm. During melt extrusion, the film was discharged from the T die onto a cooling roll maintained at 110 ° C. to produce a melt extruded film. The thickness of each layer was adjusted by adjusting the discharge amount of the single screw extruders A and B.

[0191] [Table 6]

[0192] As shown in Table 6, the physical properties of the melt-extruded films of Samples 41 and 42 were comparable to those of the melt-extruded film of Sample X3. The melt-extruded film of Sample 41 had a urethane resin content of 0.02% by mass. The melt-extruded film of Sample 42 had a haze value inferior to that of the melt-extruded film of Sample X3. The press film of Sample 42 had a urethane resin content of more than 0.02% by mass. Sample 41 had a total light transmittance, haze value, and YI superior to those of Sample 42. In Samples 41 and 42, the urethane resin was contained only inside the melt-extruded film in the thickness direction, and was not contained in the area exposed to the surface.

[0193] [Removal of primer layer and preparation of pressed film] (Sample 51) The surface of the optical film (1F) of sample 5-1 was scraped with sandpaper to remove the primer layer. Then, foreign matter on the optical film was removed with compressed air. Furthermore, foreign matter on the optical film was removed with a Technek hand roller to obtain an optical film from which the primer layer had been removed. The optical film from which the primer layer had been removed was crushed into squares, melted, and molded to obtain pellets (1E) related to sample 51. The presence or absence of the primer layer was confirmed by measuring the thickness of the primer layer using FT-IR.

[0194] Next, the pellets (1C) and the pellets (1E) were mixed in a weight ratio of 7:3 to obtain a mixture. Except for using this mixture, a (meth)acrylic resin film according to Sample 51 was obtained in the same manner as Sample 3-1. The (meth)acrylic resin film according to Sample 51 was a pressed film. The thickness of the pressed film according to Sample 51 was 150±10 μm.

[0195] The pressed film of Sample 51 had a total light transmittance of 91.9% and a haze value of 0.8%.

[0196] [Removal of primer layer and preparation of solution-cast film] (Sample 61) The primer layer was removed from the surface of the optical film (1F) of sample 5-1 in the same manner as sample 51. The optical film from which the primer layer was removed was crushed into squares and dissolved in dichloromethane to prepare a dope solution with a solid content of 20 mass%. The obtained dope solution was passed through a polypropylene pleated filter (125L-SHP-030, manufactured by ROKI TECHNO CO., LTD.) with a filtration accuracy of 3.0 μm, and then degassed.

[0197] Next, the dope solution was dropped onto a polyethylene terephthalate (PET) film and coated to a film thickness of 800 μm using an applicator. The PET film was then placed in a dryer and dried at 40° C. for 30 minutes, and then dried at 60° C. for 30 minutes. The coated film was then peeled off from the PET. The obtained film was hung in a dryer with wide mountain-shaped clips attached to the top and bottom to prevent curling, and then dried at 100° C. for 12 hours to obtain a solution-cast film according to Sample 61. The thickness of the solution-cast film was 100 μm.

[0198] The solution cast film of Sample 61 had a total light transmittance of 92.4% and a haze value of 0.1%.

[0199] (Sample 62) Except for not removing the primer layer, we tried to produce a solution-cast film in the same manner as Sample 61. However, when passing the dope through the filter, the filter immediately became clogged, so the dope could not be filtrated stably. [Industrial Applicability]

[0200] According to the present invention, the optical film can be reused. The optical film of the present invention is suitable for use in various protective films such as a polarizer protective film, a retardation film, and a polarizing film. [Explanation of symbols]

[0201] 1 Optical film 2. (Meth)acrylic resin film 3 Primer layer 4 First layer 5 Second layer 6 Third layer

Claims

1. A step of obtaining a (meth)acrylic acid ester monomer by depolymerizing an optical film having a (meth)acrylic resin film and a first primer layer laminated thereon; a step of polymerizing the (meth)acrylic acid ester monomer or a monomer group including the (meth)acrylic acid ester monomer and a monomer other than the (meth)acrylic acid ester monomer to obtain a recycled (meth)acrylic resin; A method for producing a recycled (meth)acrylic resin, comprising:

2. 2. The method for producing a recycled (meth)acrylic resin according to claim 1, wherein in the step of obtaining the (meth)acrylic acid ester monomer, the (meth)acrylic acid ester monomer is obtained by distillation after depolymerization of the optical film.

3. The method for producing recycled (meth)acrylic resin according to claim 1 , wherein the (meth)acrylic acid ester monomer comprises methyl methacrylate.

4. A method for producing recycled (meth)acrylic resin as described in claim 1, wherein the first primer layer contains at least one binder resin selected from a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin.

5. Obtaining a recycled (meth)acrylic resin by the method of claim 1; forming the recycled (meth)acrylic resin into a recycled (meth)acrylic resin film; A method for producing a recycled (meth)acrylic resin film, comprising:

6. Obtaining the recycled (meth)acrylic resin film by the manufacturing method according to claim 5; laminating a second primer layer onto the recycled (meth)acrylic film; A method for producing a recycled optical film, comprising:

7. A method for producing a recycled optical film as described in Claim 6, wherein the second primer layer contains at least one binder resin selected from a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin.